Religious Humanism Synergy to Develop Creative Industry-Based Halal Tourism in Indonesia - Fariana, Andi; Saripudin, Saripudin; Rukmana, Ovalia (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2022)
his study aims to propose a halal tourism model by adopting religious humanism integrated with the creative industry as a baseline. This is a legal study with a statutory approach, relying on various laws and regulations as the primary data, including MUI’s fatwas. This study found that religious humanism can be integrated into the development of the halal tourism industry based on creative industries, with Regional Regulations (Perda) as the guideline. The integration of religious humanism in development is possible with the participation of all stakeholders. This is because the development of halal tourism is not merely about tourism objects but also the community. In this case, religious people easily accept the idea and are willing to participate as long as the integration is structured. Abstrak. Studi ini bertujuan menawarkan model wisata halal dengan meng adopsi humanisme religius dan mengintegrasikannya dengan industri kreatif. Penelitian dilakukan dengan pendekatan perundang-undangan dengan data primer yang berasal berbagai peraturan perundang-undangan, termasuk fatwa MUI. Kajian ini menemukan bahwa humanisme religius dapat diintegrasikan dalam pengembangan industri wisata halal berbasis industri kreatif, dengan menggunakan Peraturan Daerah (Perda) sebagai pedoman. Mengintegrasikan humanism religi dengan pembangunan dimungkinkan dengan partisipasi seluruh pemangku kepentingan. Hal ini karena pengembangan wisata halal tidak hanya mengenai objek wisata tetapi juga masyarakat. Umat beragama mudah menerima gagasan dan mau berpartisipasi asalkan integrasi dilakukan secara terstruktur.